ANALYTICAL METHOD DEVELOPMENT OF ZALEPLON AS BULK DRUG AND FORMULATION USING CHROMOGENIC REAGENTS. - NIHAR RANJAN DAS; DR. G. VIDYASAGAR (International Journal of Pharma and Bio Sciences, 2013)
Two simple, economic, sensitive and reproducible and rapid spectrophotometric & chromatographic methods have been developed and validated for the determination of Zaleplon (Zpl) in capsules and as bulk drug. The methods are based on the reduction of ferric chloride by Zpl in neutral medium and subsequent chelation of iron (II) with 1, 10-phenanthroline (phen) (method A) or 2, 2Î„-bipyridyl (bipy) (method B). The resulting red colored chromogens are measured at 490 and 480 nm, for method A and method B, respectively. Under the optimum conditions, Beer’s law is obeyed in the concentration ranges of 0.25-4.0 and 2.5-50 μg ml-1 with molar absorptivity values of 5.30 x 100 and 0.780 x 100 l mol-1cm-1 and Sandell sensitivities 0.007 and 0.051 μg cm-2 for method A and method B, respectively. The results of the analysis have been validated statistically and by recovery studies.